Strategi Kepemimpinan: Quality Continuous Improvement SMP Islam Prestasi Al Mubtadi-Ien Bantul Yogyakarta - Nora Saiva Jannana (Lembaga Sosial Rumah Indonesia, 2021)
The principal's leadership becomes a reference for managing other school resources for school development. The role of the principal is very important for school quality control work. This article aims to provide a specific description of the principal's leadership strategy in sustainable quality assurance. The method used is qualitative with data collection techniques in the form of interviews, observations, and documentation. The research was conducted at the Islamic Achievement Middle School in Bantul, Yogyakarta. This school is interesting because it tries to combine the concept of multiple intelligence with the pesantren-style school system. The results of the study indicate that the strategy used by the principal can have an effect on school development. Although in practice it has not yet reached the level of activity in the theoretical structure of PDCA (Plan Do Check Action), the principal continues to develop school quality.